PENCARIAN POLA DATA SEKUENSIAL KLIMATOLOGI UNTUK PREDIKSI LUAS GENANGAN BANJIR - Suwarningsih, Wiwin; Suryawati, Endang (Teknologi Indonesia, 2011)
This research will explain how to fi nd the pattern of climate data to help predict flood inundation areas caused by the rain. Methods to be used is the order of enumeration with Lattice theory approach to the enumeration sequence to perform the operation JOIN and MEET to produce a sequence that has undergone the process of intersection with the id-list containing an equivalent class, but this theory also do a search on the show DFS and BFS to produce a event frequent or not. The end result of this research is the sequence of flood events with a large puddle of water that often arise which can be used to simulate the broad prediction of inundation caused by flood.